Marital Infidelity and Paternity Dispute in Nigeria: an Islamic Perspective - Obalowu, Issah Abeebllahi; Abdul Rahim, Adibah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
According to the statistics revealed by the geneticists, there is a rapid and drastic increment in the number of parents that carry out a DNA test to determine the real biological father of their children, whom they have been nurturing for many years. The phenomenon is said to have resulted from the rampant marital infidelity among Nigerians. So, this paper is an attempt to explore the reason for such widespread marital infidelity, the means of curbing it and investigate the Islamic perspective on a DNA test for affirming paternity, and the extent to which the father under whose roof the child was born is compelled with the result of such test. So, the qualitative method is being employed to carry out the research by revisiting the classical literature related to the issue and collecting the data from relevant sources with adequate analysis. After a thorough investigation, the result of the study shows that the major reason for the widespread marital infidelity can be related to the prevailed un-Islamic system of establishing affairs between both sexes by having premarital relationships and intimacy with the opposite sex which usually continues after legal marriage. It also reveals that, based on Islamic jurisprudence, neither a DNA test nor other means of proof can deny the legal husband paternity of a child born under his matrimonial custody and give fatherhood to an adulterer.